The effectiveness of the use of electronic multimedia activities to develop academic skills among students of the first grade intermediate with intellectual disabilities who are capable of learning in Al-Kharj Governorate - Albarrak, Sara Nasser (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the effectiveness of the use of electronic multimedia activities to develop academic language skills among students of the first grade average with intellectual disabilities who are capable of learning in Al-Kharj Governorate, and the study used the semi-experimental approach based on one group, and the sample of the study consisted of (10) of the students of the first grade average with intellectual disabilities who are amenable to learning in Al-Kharj Governorate, and the study used the academic skills test consisting of (55 questions) in both written and oral parts, and the test was applied before the use of electronic activities Multimedia and thereafter, the study found the effectiveness of the use of electronic multimedia activities to develop academic skills among students of the first grade intermediate with intellectual disabilities who are capable of learning in Al-Kharj Governorate, and the study recommended the need to activate the use of electronic multimedia activities, and suggested further studies on the subject.